2014
DOI: 10.1021/la404918b
|View full text |Cite
|
Sign up to set email alerts
|

Monolayer Properties of Asymmetrically Substituted Sexithiophene

Abstract: We present a structural comparison of monolayers on a SiO2 substrate of two asymmetrically substituted sexithiophenes (6T). Molecule 1 consists of 6T with a branched alkyl chain at one end only and shows a crystalline structure. In molecule 2, the bifunctional 6T has in addition at the other end a linear alkyl chain. It displays thermotropic liquid crystalline (LC) behavior. Both compounds form readily single molecular layers from solution. Remarkably, full monolayer coverage can be achieved before multilayer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 41 publications
3
12
0
Order By: Relevance
“…This pattern was comparable to the sexithiophene‐based structure investigated previously . a Here, surface‐attached but loosely packed oligothiophene tilted from the surface normal showed an absorption peak for sexithiophene similar to that found by previous observation . Additionally, Garnier et al also reported that the electrochemical polymerization of terthienyl resulted in sexithiophene as the major product after their coupling into a correspondingly less reactive hexamer.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…This pattern was comparable to the sexithiophene‐based structure investigated previously . a Here, surface‐attached but loosely packed oligothiophene tilted from the surface normal showed an absorption peak for sexithiophene similar to that found by previous observation . Additionally, Garnier et al also reported that the electrochemical polymerization of terthienyl resulted in sexithiophene as the major product after their coupling into a correspondingly less reactive hexamer.…”
Section: Resultssupporting
confidence: 88%
“…In fact, it was observed that the intrinsic reactivity of oligomeric radicals decreased rapidly as their conjugation length increased. Furthermore, with the lower energy threshold of the absorption spectra of the crosslinked polymer brush, the energy band gap was calculated to be 3.3 eV; this correlated well to the reported value of 3.23 eV for sexithiophene . IR spectroscopy also supported terthiophene coupling.…”
Section: Resultssupporting
confidence: 80%
“…For 7T the overall monolayer picture is rather similar as reported previously for substituted sexithiophenes. 7 For the 7T monolayer we find two main peaks assigned as hk=11 (q  =10.82 nm -1 , q z =7.09 nm -1 ) and hk=20 (q  =7.2 nm -1 , q z =11.6 nm -1 ). Using the total length of the thiophene core of 26.7 Å, the projection on the z-axis then equals 26.7×cos58 o =14 Å.…”
Section: Grazing-incidence Diffraction Of Mono-and Multilayersmentioning
confidence: 78%
“…This can be reached, for example, by either tilting one unit with respect to the other or by (partial) overlapping (interdigitation). 6,7 In such a situation a fundamental difference arises between bulk and thin-film structures:…”
Section: Introductionmentioning
confidence: 99%
“…by incorporation of dissimilar substituents into the various positions of the carbo-or heterocyclic moiety of monomer, by the asymmetry of a central core or by creation of asymmetric periphery. [37][38][39] Besides, the asymmetry of a molecule structure always affects the packing mode of compounds; for example, the oligothiophenes with different terminal aliphatic substituents have been found to form a liquid crystal phase even at an ordinary temperature that is a result of a molecular asymmetry. 40 As part of our ongoing work 36,40 we have prepared a series of asymmetrical 4,6-diaryl-substituted 2-alkoxypyrimidines integrating in one molecule two different electron excessive heterocyclic moieties (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%